Effect of Variable Confining Pressure on Cyclic Triaxial Behavior of K0-consolidated Soft Marine Clay - Lei Sun (Salehan Institute of Higher Education, 2018)
The effect of variable confining pressure (VCP) on the cyclic deformation and cyclic pore water pressure in K0-consolidated saturated soft marine clay were investigated with the help of the cyclic stress-controlled advanced dynamic triaxial test in undrained condition. The testing program encompassed three cyclic deviator stress ratios, CSR=0.189, 0.284 and 0.379 and three stress path inclinations ηampl=3,1 and 0.64. All tests with constant confining pressure (CCP) and variable confining pressure (VCP) have identical initial stress and average stress. The results were analyzed in terms of the accumulative normalized excess pore water pressure rqu recorded at the end of each stress cycle and permanent axial strain, as well as resilient modulus. Limited data suggest that these behavior are significantly affected by both of the VCP and CSR. For a given value of VCP, both of the pore water pressure rqu and permanent axial strains are consistently increase with the increasing values of CSR. However, for a given value of CSR, the extent of the influence of VCP and the trend is substantially depend on the CSR.